Increasing the Business Potential of MSMEs through the Utilization of Digital Bookkeeping and Digital Marketing in Sebatik Island - Eka Indriyani MS; Wahidah Abdullah; Eka Suhartini; Rika Dwi Ayu Parmitasari; Alim Syariati; Miftha Farild; Rusnawati (International Journal Of Community Service, 2024)
The characteristics of the Indonesian economy are supported by the micro, small, and medium enterprise sectors, which account for 98.33% of the enterprise population in Indonesia. This is evidenced by the increasing number of business units, labor contribution, and contribution of MSMEs to GDP. The post-COVID-19 pandemic has brought major changes to the lifestyle of businesses and consumers along with the use of digitalization. The existence of digitalization provides opportunities for businesses to increase online sales and fast and efficient bookkeeping. The obstacles faced at this time are that Sebatik Island MSME actors still have obstacles in utilizing digital applications. Therefore, this research began by conducting community service on 13 September 2023 to provide training on digitalization to business actors. The samples in this study were 27 MSME actors dominated by culinary businesses. The methods used include mapping, interviews with UMKM participants, formulation of problems and solutions, determination of problem-solving strategies, and implementation of MSMEs seminars.